AN ANALYSIS OF THE MAIN CHARACTER IN THE FILM â€œTHE NIGHTINGALEâ€: A LITERARY PSYCHOLOGY STUDY - Putri, Mardiani Sela; Dahniar, Dahniar; Halim, Nur Mutmainna; Bustang, Bustang (Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This research was conducted to identify and analyze the main character of The Nightingale film using a literary psychology approach with the objective to analyze the depiction of the main character. This was a qualitative method. In obtaining the data, this research was conducted by watching The Nightingale film several times and analyzing Clare as the main character in the film. The researcher also uses the theory of emotionâ€™s classification from David Krech. Results of the research found out that Clare as the main character of The Nightingale film had carried seven classifications of emotions, those data were one datum of guilt concept, two data of penetrated guilt, two data of punishing yourself, one datum of shame, four data of sadness, four data of hatred, and three data of love. From those 7 classifications, it was dominated with hatred concept. This proves that the driving force that causes change is very strong compared to other concepts. It can be seen from the storyline of the main character in The Nightingale film, that Clare's character was actually a kind person, but unfortunately she was always treated badly by people around her. This is the reason why Clare was full of resentment and determined to take a revenge for all kind of miserable things she went through.